The Impact of R&D Investments on Market Values: A Comparison between the UK and US - LIU, Qiujuan (2017)
This paper investigates the impact of R&D investments on market values by using both the UK and US firms during the latest ten years, 2007-2016, hoping to find out the most recent impact of R&D investments on firm’s market value. In addition, this paper is trying to examine the impact differences of R&D investments on market values between the technology and non-technology firms, and mature and young firms in the UK and US, respectively. After controlling for firm size, free cash flow, leverage, growth and profitability, the results show that R&D investments are positively and significantly associated with firm’s market value, no matter the firm is in the UK or US. Besides, I also find that the impact of R&D investments on market values is significantly more positive for non-technology firms than that for technology firms in both the UK and US. Furthermore, in UK, the impact of R&D investments young firms’ market values is significantly more positive than mature firms. While in US, the situation is opposite; that is, the impact of R&D investments on mature firms’ market values is significantly more positive than that on young firms. Finally, the empirical findings of this study can also shed some light for corporate managers, investors and standard setters.